Adherence to the 2010 American College of Cardiology Foundation Appropriate Use Criteria for Cardiac Computed Tomography: Quality Analysis at a Tertiary Referral Center. Issue 1 (March 2016) - Sidhu, Manavjot S.; Lumish, Heidi; Uthamalingam, Shanmugam; Engel, Leif-Christopher; Abbara, Suhny; Brady, Thomas J.; Hoffmann, Udo; Ghoshhajra, Brian B.
Abstract : Background: In November 2010, the American College of Cardiology Foundation published revised appropriateness criteria (AC) for cardiac computed tomography (CT). We evaluated adherence to these criteria by providers of different subspecialties at a tertiary referral center. Methods: Reports of 383 consecutive patients who underwent clinically indicated cardiac CT from December 1, 2010, to July 31, 2011, were reviewed by physicians with appropriate training in cardiac CT. Scans were classified as appropriate, inappropriate, or uncertain based on the revised 2010 AC. Studies that did not fall under any of the specified indications were labeled as unclassified. Adherence to the AC was also analyzed as a function of provider type. Research scans were excluded from this analysis. Results: Three hundred eight exams (80%) were classified as appropriate; 26 (7%), as inappropriate; 30 (8%), as uncertain; and 19 (5%), as unclassified. Of the 19 (5%) unclassified cardiac CT exams, the most common indication was for evaluation of suspected aortic dissection. Three hundred five exams (80%) were referred by cardiologists; 73 (19%), by internists; and 5 (1%), by neurologists. Of the 305 cardiology-referred studies, 221 (73%) were ordered by general cardiologists; 28 (9%), by interventional cardiologists; and 56 (19%), by electrophysiologists. There was no significant difference in adherence to the criteria between provider specialties or between cardiology subspecialties ( P > 0.05). Conclusions: high across provider specialties.